Verflochtene Nationsbildung - Liebisch-Gümüş, Carolin (2020)
The book tells the history of Turkish nation-building after the First World War from a global historical perspective. The author focuses on the relationship between Turkish nationalists and the League of Nations. She demonstrates the ideas, interactions, and structures that linked the nationalist project with Geneva internationalism, thereby revealing connections between national and global order.